Effect of carbon black with large particle size on dynamic mechanical analysis of magnetorheological elastomers (MREs). (17th August 2018) - Lu, Huanglei; Wang, Wenju; Yang, Fufeng; Wang, Guoping; Rui, Xiaoting
Abstract: Magnetorheological elastomers (MREs) are composite materials consist of micron-sized magnetizable particles and a polymer matrix. In this work, we chose the most suitable carbon black (CB) by comparing MR effect of MREs with three kinds of CB (N330, N660, N990). To improve magneto-rheological (MR) effect, MREs with different contents of CB were prepared. MRE samples were fabricated under a constant magnetic field. The rheological properties including MR effect, damping ratio were measured with rotational rheometer. The effect of loading parameters such as shear strain, frequency and magnetic field on the shear modulus and damping ratio of MREs were observed. The experimental results show that N990 is better at improving MR effect than N330 and N660. N990 improve the damping performance of MREs. The magneto-rheological properties increase with the increase of N990 content. This type of MREs with varied stiffness and damping have potential as semi-active control devices for smart damping materials.